PENERAPAN MODAL SOSIAL DALAM PRAKTEK PERADILAN YANG BERBASIS KEPEKAAN SOSIAL - Zaka Firma Aditya (Legality : Jurnal Ilmiah Hukum, 2017)
The judiciary is an institution that should reflect on justice sought by justice seekers. But the fact is different; justice becomes one of the institutions with a high level of public distrust. The actual social capital has been present and is present in the community but has not yet been functioned and used further, especially by law enforcement officers making law enforcement in Indonesia far from expectations. In fact, the concept of modern justice has been triggered at international meetings that not only prioritize formal legal aspects but also the intellectual, emotional and spiritual aspects of law enforcement as well as social capital. In an effort to bring about a legal state with progressive legal practice will greatly depend not only on good legislation but much more dependent on law enforcement officials as implementers of the law